Peran Guru BK dalam Manajemen Program Bimbingan dan Konseling di Sekolah - Fitria Umami; Firman; Neviyarni (Medan Resource Center, 2022)
Schools must make programs where educational programs are able to foster students to face the times. For this reason, counseling teachers also have a role in managing educational programs, especially in the field of guidance and counseling. Guidance and counseling management are all efforts or methods used to optimally utilize all components or resources (manpower, funds, facilities/infrastructure) and information systems in the form of a set of guidance data to provide guidance and counseling services in order to achieve goals. The purpose of this study is to find out the role of BK teachers in managing the guidance and counseling program in schools. This research method uses a literature study. The results showed that the counseling guidance teacher had an important role in designing the management of the counseling guidance program. To design the program, it is necessary to have the competence and qualifications of BK teachers. The most urgent thing in making management is that BK teachers need to carry out assessments on students. If the assessment is correct, the counseling guidance program is also good.